Svet algoritmov pri predmetu šport v I. vzgojno-izobraževalnem obdobju osnovne šole - Časar, Igor (Revija inovativna pedagogika, 2025)
A stimulating learning environment, where abstraction, decomposition, generalization, and pattern recognition play a central role, enables pupils to develop fundamental computer science and informatics knowledge. This paper presents a case study of an innovative teaching practice that develops the concept of algorithms in pupils in the first educational cycle. The research examines how integrating pictograms into physical education can contribute to the development of fundamental computer science knowledge in pupils in the first educational cycle. The research aims to analyze teaching approaches, methods, and the effects of integrating computational tools into classroom instruction, considering the Framework for Computer Science from Preschool to Secondary School and the Physical Education curriculum. Data was collected using qualitative methods. The case study was conducted on a targeted small sample of a homogeneous group of pupils from the bilingual primary school Genterovci, aged 7 to 9. The data was collected through observation, product analysis, and semi-structured interviews. Data analysis was conducted using thematic analysis. The analysis of the responses showed that, within a stimulating learning environment, it is possible to develop fundamental computer science knowledge without using digital devices. Pupils were able to describe the problem more easily, identify key details, and find solutions. Pupils had no difficulty recognizing and creating algorithms. Collaborative learning was further developed by forming teams and assigning roles, encouraging experience-sharing and joint problem-solving. The findings suggest that similar methods could be applied to other subjects, opening new possibilities for integrating computational thinking into primary school education.
Keywords: algorithms; algoritmi; computer science and informatics; Informacijsko-komunikacijska tehnologija; Osnovnošolsko izobraževanje; računalništvo in informatika; spodbudna učna okolja; stimulating learning environments; Športna vzgoja